Accounting principles and procedures for a sole proprietorship (volume 1 - service) : a textbook for the first course in accounting - Monte-Galanza, Raquel (Quezon City, Philippines : Rex Printing Company, Inc., 2003)
Accountancy has become a separate curriculum from business and commercial courses. This book aims to meet the need of accountancy students for a textbook that contains a comprehensive explanation of accounting principles and procedures applicable to a sole proprietorship.
Chapter 1. The Accounting Fundamentals -- Chapter 2. The Recording Process -- Chapter 3. The Posting Process -- Chapter 4. Preparation of the Trial balance -- Chapter 5. Preparation of Adjusting Entries -- Chapter 6. Worksheet -- Chapter 7. Preparation of Financial Statements -- Chapter 8. Closing Entries -- Chapter 9. Post-Closing Trial Balance -- Chapter 10. Reversing Entries.
Includes index.
Keywords: ACCOUNTANCY -- PROPRIETORSHIP